2022
DOI: 10.3390/life12081214
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Methane Production from Pelagic Sargassum Using Combined Pretreatments

Abstract: The constant golden tides of Sargassum spp., identified to be a mixture of Sargassum natans and Sargassum fluitans, observed recently in the Mexican Caribbean have affected the marine ecosystem and the local economy and have created the need for solutions for their management and use. The Sargassum arrivals have thus been considered as third-generation feedstock for biofuel. Their potential for energetic conversion to biomethane was investigated, with hydrolysis as the limiting step due to its complex composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Regarding CHNS elemental analysis results, a percentage of carbon content of 34.15% was obtained in the samples of the Sargassum consortium collected offshore (AL), which is similar to those reported by other authors [27,49]. As for the AB, DB, and PL samples, they presented a carbon content of 27-28% similar to that reported by [26]; however, as for the C:N ratio, in AL and PL, a ratio of 24:1 was obtained, which falls in the ideal range for the optimal digestion or fermentation of organic matter [27], which does not happen with samples collected in AB and DB as they have a C:N ratio of less than 20:1.…”
Section: Variation Of Volumes Per Year and Per Sitesupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding CHNS elemental analysis results, a percentage of carbon content of 34.15% was obtained in the samples of the Sargassum consortium collected offshore (AL), which is similar to those reported by other authors [27,49]. As for the AB, DB, and PL samples, they presented a carbon content of 27-28% similar to that reported by [26]; however, as for the C:N ratio, in AL and PL, a ratio of 24:1 was obtained, which falls in the ideal range for the optimal digestion or fermentation of organic matter [27], which does not happen with samples collected in AB and DB as they have a C:N ratio of less than 20:1.…”
Section: Variation Of Volumes Per Year and Per Sitesupporting
confidence: 90%
“…Results determined for these parameters by species indicated in both species that the highest values belong to the AL site and they decreased among the sites getting closer to the coast (AB, DB, and PL), and each parameter range remains in the same magnitude; see Table 6. Regarding the BOD/COD relationship, the results are lower than those reported for the consortium; thus, biodegradability would remain low [2,27]. The BOD/COD ratio is similar between AL and PL sites, as well as AB and DB, with values less than 0.1 (Tables 5 and 6) for 2020 compared to 2021, for which the same sites have a lower ratio.…”
Section: Biodegradability By Species: S Natans and S Fluitansmentioning
confidence: 67%
“…When these results were compared with the untreated feedstock, it was observed that mechanical pretreatment with peroxide improves the methane yield by 7.19%, whereas the combination of mechanical and biological pretreatment reduced methane yield by 23.03%. 124 This difference in their influence can be linked to the ability of T. hirsuta to solubilize the feedstock beyond normal, thereby losing some of the organic matter meant for methane production to the pretreatment process. The impacts of thermal, chemical, and thermochemical pretreatment methods experimented on P. palmata was observed that thermal pretreatment at temperatures of 20, 70, 85, and 12 °C does not significantly impact the methane yield.…”
Section: Comparison Of Pretreatment Methodsmentioning
confidence: 99%
“…It was observed that mechano-chemical pretreatment enhanced the methane yield by 7.19%, but mechano-biological treatment reduced the methane yield by 23%. 124 Mechanical pretreatment was combined with nanoparticle additive during the pretreatment of Ulva intestinalis linneaus, and it was discovered that methane yield was improved by 366.7%. 99 This is an indication that not all combined pretreatments can improve the methane yield of all macroalgae.…”
Section: Macroalgae Pretreatmentmentioning
confidence: 99%
See 1 more Smart Citation